AB0065 Possible Interplay Between Serum Amyloid-A and Pro-Inflammatory Cytokines Into the Pathogenesis of Behçet's Disease. (9th June 2015) - Lopalco, G.; Lucherini, O.M.; Cantarini, L.; Vitale, A.; Talarico, R.; Giannini, M.; Scioscia, C.; Anelli, M.G.; Cacciapaglia, F.; Natuzzi, D.; Bizzoca, R.; Perniola, S.; et al.
Abstract : Background: Behçet's disease (BD) is a multi-systemic disorder of unknown aetiology characterized by relapsing oral–genital ulcers, uveitis, and involvement of vascular, gastrointestinal, neurological and musculoskeletal system. Although disease pathogenesis is still unclear, the main actors seem to be genetic background and activation of both innate and adaptive immunity ensuing in an interaction between T lymphocytes and neutrophils. Indeed, multiple pro-inflammatory cytokines are involved in different pathogenic pathways that eventually lead to tissue damage in BD. Objectives: The aims of our study were to evaluate serum cytokines levels of IL-8, IL-18, IFN-α2a, IL-6, IFN-γ, CXCL10, CXCL11, CXCL9 and SAA levels in patients with BD, in comparison to healthy controls (HC), and to correlate their levels to disease activity. Methods: The study included 78 serum samples obtained from 58 BD patients. We analysed a set of pro-inflammatory cytokines including IL-8, IL-18, IFN-α2a, IL-6, IFN-γ, CXCL10, CXCL11 and CXCL9 by multiplex bead analysis as well as SAA by ELISA. Results: Compared to HC, BD patients showed elevated cytokine levels of IL-8 (p=0.0001), IL-18 (p=0.0058), IFN-α2a (p=0.0181) and IL-6 (p=0.0233), and low levels of CXCL11 ( p =0.0369) (Table 1 ). When BD patients were divided into active and inactive group, we observed enhanced IL-8 and IL-18 in both groups compared to HC, while IFN-α2a ( p =0.0141) and IL-6 ( p =0.0332) were raised in active group compared to HC. Moreover, CXCL11 ( p =0.0154) serum concentrations were significantly lower in inactive-BD than HC (Table 1 ). In the second part of the study, we compared serum cytokine profiles between BD patients with SAA serum levels ≤20 mg/L (negative-SAA), >20 mg/L (positive-SAA) and HC. Interestingly, we observed that positive-SAA BD patients showed higher levels of inflammatory markers than HC or negative-SAA group. Among these cytokines, IL-18, IFN-α2a and IL-6 were higher in positive-SAA BD group than HC whilst IL-8 and CXCL9 levels were higher than in negative-SAA and HC (Table 1 ). Conclusions: BD patients exhibited elevated levels of inflammatory mediators, more evident in active disease and positive-SAA group, suggesting that may exist a relationship between SAA and pro-inflammatory cytokines in the intricate scenario of BD pathogenesis. References: Hatemi G, Yazici Y, Yazici H. Behçet's syndrome. Rheum Dis Clin North Am 2013; 39:245–61. Hamzaoui K, Hamzaoui M, Guemira F, Bessioud M, Hamza M & Ayed K. (2002) Cytokine profile in Behcet's disease patients. Relationship with disease activity. Scand J Rheumatol 31: 205-10. Uhlar CM, Whitehead AS. Serum amyloid A, the major vertebrate acute-phase reactant. Eur J Biochem. 1999 Oct;265(2):501-23. Nara K, Kurokawa MS, Chiba S et al. Involvement of innate immunity in the pathogenesis of intestinal Behcet's disease. Clin Exp Immunol 2008;152:24551. Disclosure of Interest: None declared